Avian Influenza A Viruses: Evolution and Zoonotic Infection - Kim, Se Mi; Kim, Young-Il; Pascua, Philippe Noriel Q.; Choi, Young Ki (Seminars in Respiratory and Critical Care Medicine, 2016)
Although efficient human-to-human transmission of avian influenza virus has yet to be seen, in the past two decades avian-to-human transmission of influenza A viruses has been reported. Influenza A/H5N1, in particular, has repeatedly caused human infections associated with high mortality, and since 1998 the virus has evolved into many clades of variants with significant antigenic diversity. In 2013, three (A/H7N9, A/H6N1, and A/H10N8) novel avian influenza viruses (AIVs) breached the animal-human host species barrier in Asia. In humans, roughly 35% of A/H7N9-infected patients succumbed to the zoonotic infection, and two of three A/H10N8 human infections were also lethal; however, neither of these viruses cause influenza-like symptoms in poultry. While most of these cases were associated with direct contact with infected poultry, some involved sustained human-to-human transmission. Thus, these events elicited concern regarding potential AIV pandemics. This article reviews the human incursions associated with AIV variants and the potential role of pigs as an intermediate host that may hasten AIV evolution. In addition, we discuss the known influenza A virus virulence and transmission factors and their evaluation in animal models. With the growing number of human AIV infections, constant vigilance for the emergence of novel viruses is of utmost importance. In addition, careful characterization and pathobiological assessment of these novel variants will help to identify strains of particular concern for future pandemics.
Keywords: avian influenza A virus; humans; pathogenicity; transmission; pandemic; influenza vaccines